Zero Tolerance, the media, and a local community - Törrönnen, Jukka (Journal of Scandinavian studies in criminology and crime prevention, 2004)
The article examines a one-year zero tolerance project launched by the City of Tampere in southern Finland in August 1999 with a view to discouraging drunken and disorderly behaviour in public places. The analysis is anchored to the context of publicity produced by the local daily Aamulehti. The project is approached from a constructionist vantage point by asking what kinds of techniques and programmes of responsibilization and punishment were articulated for the programme in Aamulehti, which of them gained a dominant position in the local publicity and how the different 'versions' of the programmes and techniques were articulated as part of the local actors' self-understanding. The tools of analysis are mainly borrowed from positioning theory. The articles appearing in Aamulehti on zero tolerance are analysed in terms of a struggle over meaning in which the community position of zero tolerance and the social identities of the actors involved are shaped by deconstructing and reconstructing categories, by redirecting the objectives of the campaign and by manipulating identification mechanisms. The meaning struggle waged around zero tolerance is understood as a bargaining process over what kind of moral order the community needs